The Origin of Minangkabaunese People’s Ancestors Shown in the Speech “Pasambahan Maanta Marapulai” Produced by ELTA Record Bukittinggi - Agustrinaldi Naldi; Saunir Saun (English Language and Literature, 2020)
The purpose of this research was to describe the origin of Minangkabaunese people’s ancestors shown in the speech “Pasambahan Maanta Marapulai” produced by ELTA Record Bukittinggi. This research discussed about the origin of Minangkabaunese on that video based on myth. The researcher used the descriptive qualitative method. It was a method that researched an object by explaining it. The researcher collected the supporting data from some books; those are literature books, journals and another books that related with this research. In analyzing the data, researcher described the implicit meaning from the speech of “Pasambahan Maanta Marapulai”. It was the speech from the groom’s family and the bride’s family. The result of this research told that the origin of Minangkabaunese was the third son of Sultan Iskandar Zulkarnain named Maharaja Diraja. He sailed through Hindia Ocean. He found a piece of land in the west of Sumatera which he called Perca island or known as Minangkabau. Maharaja Diraja saw Mount Merapi, and then his group and he went to the top of that mount. They built a village there firstly named Siligundi Nan Baseloin Pariangan Padang Panjang. Based on the analysis of the story about the origin of Minangkabaunese in the speech”Pasambahan Maanta Marapulai”, the researcher concluded that the story was the myth.